Opting out of the social contract: tax morale and evasion - Castañeda, N; Doyle, D; Schwartz, C (SAGE Publications, 2019)
We examine the individual-level determinants of tax morale in low-capacity states, specifically Latin American countries, where the social contract is often perceived as fractured. We argue that individuals in such states perceive the social contract as an agreement to which they can opt in or opt out. Those who choose to opt out prefer to substitute state-provided goods for private providers, rather than pay for public goods through taxes or free-ride to receive those goods. Through a list experiment conducted in Mexico City, we demonstrate that willingness to evade taxes is highest when individuals have stepped outside of the social contract. More traditional indicators of reciprocity – such as socio-economic status and perceptions of corruption – are not significant. We bolster our experimental results with observational data from seventeen Latin American cities; those with access to employer-sponsored insurance are more willing to evade tax.